Respuesta :

caylus
Hello,

3a/7+5=11
==>3a/7=11-5
==>3a/7=6
==>3a=6*7
==>3a=42
==>a=42/3
==>a=14

This is a two-step equation, and it looks like you've figured out the first part.

So, for the second part.

     3a/7 + 5 = 11
3a/7 + 5 - 5 = 11 - 5  <---(subtract 5 from both sides of the equal sign)
      3a/7 + 0 = 6
                3a = 6 x 7 <---(there is a variable and three, and there is 7, so to                                                make it easier to calculate you shift the seven to the                                            other side of the equal sign and multiply it with the 6)
                 3a = 42
                   a = 42/3 <---( there is a variable and there are numbers. To make                                              it equal, you shift the 3 to the other side of the equal                                              sign so that numbers remain on one side and                                                         variables remain on the other side.)
                   a = 14